An Empirical Relationship between Stress and Job Performance: A Study with Private School Teachers (Indian Journal of Public Health Research & Development, 2020)
Stress reacts in the human body with physical, mental and emotional responses. It may be positive or negative. Negative stress affects the concern person and the environment also. It is part of our body. Stress can experience stress from our environment, body, and thoughts. The main purpose of this study is to find the factors causing stress among the teachers working in private schools. The researcher used linear regression analysis to find the result. The results show that the main factor causing stress are role conflicts and Pay. The stress and job performance are negatively correlated. Stressful teachers not performed well compared with other teachers.
Keywords: Stress, Job Performance, Role conflicts